Desenvolvimento e estabilidade de sistemas microemulsionados contendo óleos vegetais - Torres, Maycon de Paula Ribeiro (2018)
The study of nanostructured release systems, such as microemulsions, can optimize and / or potentiate the action of substances conveyed to them. Vegetable oils obtained from fruits of the Cerrado and Amazonia have been gaining notoriety, notably the pequi oil (Caryocar brasiliense Camb.) and bacaba oil (Oenocarpus bacaba Mart.). The evaluation of the quality parameters of the microemulsions during the stability studies contributes to the understanding of the components behavior in these formulations during their storage. Thus, this study aimed to develop microemulsion formulations containing pequi and bacaba oil, to determine its stability and to evaluate its potential antioxidant activity. Pseudoternary phase diagrams were developed, which provided 36 formulations with different proportions of water, surfactants such as sorbitan oleate (Span 80® ) and polysorbate 80 (Tween 80® ) and co-surfactant 1- butanol, capric/ caprylic acid triglycerides (Polymol 812® / TCC) and pequi oil or bacaba oil. The bacaba oil was used as the oily phase of the formulation, while pequi oil was incorporated in the proportion of 3% (w/w) in the formulations where TCC was used as the oily phase. The microemulsions were prepared and stored at room temperature for three days for further visual evaluation, observing their characteristics and possible phase separation. The selected formulations were subjected to centrifugation and evaluation of pH, conductivity and refractive index, and then the preliminary stability tests were developed, where the samples were submitted to cooling/heating cycles (5 ± 1 ° C / 40 ± 1 ° C) by 14 days. After this period the formulations were retested. The formulations approved in the preliminary stability tests were subjected to the accelerated stability test for a period of 90 days at room temperature, at 40 ± 1 ° C and at 5 ± 1 ° C, and the physicochemical parameters were analyzed every 30 days. For the formulations approved in the accelerated stability tests, hydrodynamic droplet diameter analysis, rheological profile and analysis of potential antioxidant activity were performed. After the stability tests, two of the formulations containing pequi oil and six containing the bacaba oil were approved and moved further to the next test phase. The hydrodynamic diameter tests showed that all formulations had droplet size in the nanometer range. The rheological profile showed that all the formulations presented Newtonian profile and linear viscosity. Analysis of the potential antioxidant activity of the formulations showed that the antioxidant activity of the oils was increased when it was conveyed to the formulations.